30‐day readmission following urgent and elective transcatheter aortic valve replacement: A Nationwide Readmission Database analysis. Issue 7 (19th August 2021) - Amgai, Birendra; Patel, Neelkumar; Chakraborty, Sandipan; Bandyopadhyay, Dhrubajyoti; Hajra, Adrija; Koirala, Soniya; Ghosh, Raktim K.; Aronow, Wilbert S.; Lavie, Carl J.; Fonarow, Gregg C.; Abbott, J. Dawn; Kapadia, Samir
Abstract: Background: Transcatheter aortic valve replacement (TAVR) is being increasingly used for decompensated severe symptomatic aortic stenosis. Data on urgent and elective TAVR readmission is scarce in the literature. Here, we have performed a retrospective cohort study with the Nationwide Readmission Database of 2016 to identify the rate of 30‐day all‐cause readmission, common causes of readmission, and distribution of morbidity in index admission and readmission after urgent and elective TAVR. Methods: We used International Classification of Diseases, Tenth Revision codes (02R.F38H, 02R.F38Z, 02R.F48Z) for identification of all TAVR procedures done in 2016 in patients >18 years old. We found 8379 patients who underwent urgent TAVR and 32, 006 patients who underwent elective TAVR in 2016. Result: The mean age of patients undergoing urgent TAVR was 79 ± 9.97 years with 44.6% women. The mean age of patients undergoing elective TAVR was 80.7 ± 8.25 years with 46.2% women. We found the 30‐day all‐cause readmission rate of 15.5% and 9.5% in patients undergoing urgent and elective TAVR, respectively ( p < 0.001). The cardiac cause was the predominant cause of readmission in both groups (43.77% vs. 42.11%, p = 0.57), followed by pulmonary cause, gastrointestinal (GI) cause, and renal cause. Among cardiac causes, congestive heart failure (CHF) was predominant cause of readmission and was similar in both groups (18.73 in urgent TAVR vs. 15.73 in elective TAVR, p = 0.12). Conclusion: We found that the all‐cause 30‐day readmission rate was higher in patients who had undergone urgent TAVR. Further studies are needed to better understand this difference.